PENINGKATAN USAHA BATAKO PADA KELOMPOK PINTAR AKSARA DAN TERAMPIL AKSARA - Anam, Choirul; Riptanti, Erlyna Wida; Suminah, - (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2014)
Nowadays, business in concrete brick has good prospect since it iscommonly used to build house which is recently well-known. This businessopportunity was whiffed by creative group Aksara and Terampil Aksara atGiriharjo sub-district, Puhpelem District, Wonogiri Regency. However, thisbusiness faced many obstacles in progress; they are (1) the minimum productivityof concrete brick machine; (2) less optimal business management;and (3) weak institutional. The approach methods offered to solve those problemswere (1) introduction to the technology of concrete brick machinery;(2) the improvement in business management; and (3) strengthening groupinstitutional. From those methods, the implemented activities covered:appropriate framework plan technology and introduce it to the two groups,workshop for concrete brick production, business management workshopand strengthening group institutional.The result showed that the knowledge and skill of the group membersin producing concrete brick increased significantly. It was proven bythe increase in concrete brick production up to 100 percent than the priorproduction. The average production per day was more than 300 units of concretebrick for each group. The increase in production affected that incomereceived by each member of the groups in which the increase reached 25percent of the prior income. Follow-up activity should be performed continuouslyby escorting the groups at least once a month.Keyword: concrete brick, productivity, and strengthening